A new heuristic for the quadratic assignment problem. Issue 3 (2002) - Drezner, Zvi
Abstract : We propose a new heuristic for the solution of the quadratic assignment problem. The heuristic combines ideas from tabu search and genetic algorithms. Run times are very short compared with other heuristic procedures. The heuristic performed very well on a set of test problems.